Ratio of jet cross sections at square root of s = 630 GeV and 1800 GeV. - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Alves, G; Amos, N; Anderson, E; Baarmand, M; Babintsev, V; Babukhadia, L; et al. (2001)
The D0 Collaboration has measured the inclusive jet cross section in barpp collisions at square root of s = 630 GeV. The results for pseudorapidities (eta)<0.5 are combined with our previous results at square root of s = 1800 GeV to form a ratio of cross sections with smaller uncertainties than either individual measurement. Next-to-leading-order QCD predictions show excellent agreement with the measurement at 630 GeV; agreement is also satisfactory for the ratio. Specifically, despite a 10% to 15% difference in the absolute magnitude, the dependence of the ratio on jet transverse momentum is very similar for data and theory.